Analisa Penerapan Internet Banking (Ibs Mobile) dalam meningkatkan Jasa dan Pelayanan di KSPPS BMT Artha Buana Metro Lampung - Nurohmah, Siti; Rahmawati, Rita (Bulletin of Community Engagement, 2024)
Baitul Maal Wat Tanwil is a microfinance institution whose service products help make it easier for customers or members to check their balances without coming to the office. This application is also an addition to service. Apart from services provided directly by BMT employees, this application is also a service that functions online and makes it easy to operate at any time. The aim of this research is to analyze the application of Internet Banking (Ibs Mobile) in improving services and services at Kspps Bmt Artha Buana Metro Lampung. In this research, descriptive field research (Field Riserch) was used. The research approach method uses qualitative. Data sources use primary and secondary data sources. The data collection technique is by using observation, interview and documentation techniques. The data analysis technique used is deductive by deducing general principles into specific ones. Based on the results of data analysis, KSPPS BMT Artha Buana Metro Lampung has implemented the IBS Mobile application which aims to increase competitiveness with other BMTs, keep up with current developments and increase public trust in customers. So based on this, the author concludes from the research results that at KSPPS BMT Artha Buana Metro Lampung, the implementation of the IBS Mobile application is able to improve services and services for members. Keywords: Internet Banking (Ibs Mobile), Analyzing Internet Banking